A SYSTEMATIC REVIEW ON ANALYTICAL METHOD FOR THE ESTIMATION OF FINERENONE AND EMPAGLIFLOZIN - Nidhi Nagani; Dr. Neha Tiwari; Dr. Pragnesh Patani (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
This review focuses on analytical methods for finerenone, a non-steroidal mineralocorticoid receptor antagonist, and empagliflozin, a selective SGLT2 inhibitor, used in the management of type 2 diabetes mellitus with chronic kidney disease. Accurate estimation of these drugs is essential for pharmacokinetics, clinical monitoring, and quality control. Finerenone is mainly analyzed using chromatographic techniques such as HPLC, UHPLC, and LC–MS/MS, while empagliflozin is frequently estimated by spectrophotometric, chromatographic, and hyphenated methods, with LC–MS/MS being the most sensitive in biological matrices. This review critically evaluates reported analytical approaches, comparing their applicability, advantages, and limitations, and highlights the future scope for developing robust, cost-effective, and regulatory-compliant methods.